Natural Bioactive Compounds: Technological Advancements - Sinha, Rajeshwar; Häder, Donat-Peter (Natural Bioactive Compounds - Technological Advancements, 2020)
Natural Bioactive Compounds: Technological Advancements deals with the latest breakthroughs in the field of screening, characterization and novel applications of natural bioactive compounds from diverse group of organisms ranging from bacteria, viruses, cyanobacteria, algae, fungi, bryophytes, higher plants, sponges, corals and fishes. Written by some of the most reputed scientists in the field, this book introduces the reader to strategies and methods in the search for bioactive natural products. It is an essential read for researchers and students interested in bioactive natural products, their biological and pharmacological properties, their possible use as chemopreventive or chemotherapeutic agents, and other future potential applications.
CRIS-Team Scopus Importer:2024-12-16